Retina thickness as a marker of neurodegeneration in prodromal lewy body disease. Issue 2 (11th November 2019) - Lee, Jee‐Young; Ahn, Jeeyun; Oh, Sohee; Shin, Joo Young; Kim, Yu Kyeong; Nam, Hyunwoo; Jeon, Beomseok
Abstract: Objectives: We investigated retinal change and its relationship with neurodegeneration markers in a prodromal Parkinson cohort. Methods: A total of 30 patients with idiopathic rapid eye movement sleep behavior disorder were recruited. Participants underwent olfactory testing, macular optical coherence tomography, microperimetry, contrast sensitivity test, and brain N ‐(3‐[ 18 F]fluoropropyl)‐2‐carbomethoxy‐3‐(4‐iodophenyl) nortropane positron emission tomography. We measured the ganglion cell complex thicknesses and investigated its correlation with olfactory function and striatal dopamine transporter availability. A linear mixed‐effect model was applied with adjustment for multiple comparisons. Results: The parafoveal ganglion‐cell‐complex thickness in this cohort lay between our healthy control and drug‐naïve Parkinson's disease group data. Idiopathic rapid eye movement sleep behavior disorder patients also had contrast sensitivity impairment as in Parkinson's disease with a nonsignificant change in macular sensitivities. Macular ganglion cell complex thickness correlated with olfactory scores and with striatal dopamine transporter availabilities. Conclusions: Macular ganglion cell complex thinning may be a marker of neurodegeneration in prodromal Parkinson's disease. © 2019 International Parkinson and Movement Disorder Society